Long Time Coming : Short Writings from Zimbabwe. - Morris, Jane (amabooks, 2008)
Long Time Coming brings together short stories and poems from thirty-three writers that provide snapshots of this turbulent period in Zimbabwe's history. Snapshots of living in a country where basic services have crumbled: where shops have no food, taps no water, banks no money, hospitals no drugs, bars no beer. Snapshots of characters surviving against seemingly insurmountable odds. Horrific snapshots of the abuse of power, of violence and oppression, of the destruction of dreams. But this is Zimbabwe and there are lighter moments and moments of hope: in some of life's simple pleasures, in the coming of the rains, in the wink and the smile of a stranger, in a challenge to patriarchy, in the inner strength of the people, in fighting back. The writers are Raisedon Baya, Wim Boswinkel, Diana Charsley, Brian Chikwava, Julius Chingono, Mathew Chokuwenga, Bhekilizwe Dube, John Eppel, Peter Finch, Petina Gappah, David Goodwin, Anne Simone Hutton, Monireh Jassat, Ignatius Mabasa, Fungai Rufaro Machirori, Judy Maposa, Deon Marcus, Christopher Mlalazi, Gothataone Moeng, Wame Molefhe, Linda Msebele, Mzana Mthimkhulu, Peter Ncube, Thabisani Ndlovu, Pathisa Nyathi, Andrew Pocock, John S. Read, Bryony Rheam, Lloyd Robson, Ian Rowlands, Owen Sheers, Chaltone Tshabangu and Sandisile Tshuma.